The Influence of TikTok Social Media in Islamic Religious Education in the 5.0 Era - Maulia Indana Zulfa; Ida Zahara Adibah; Isnaini Isnaini (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the influence of social media TikTok in the context of Islamic education, particularly within the 5.0 Era. The 5.0 Generation refers to a group that has grown up in the digital age, deeply connected to technology and social media, including TikTok. The primary objective of this research is to understand TikTok's role in Islamic education in the 5.0 Era and its impact on the understanding and practice of religion among this generation. This study uses a qualitative approach, conducting interviews with members of Generation 5.0 who actively use TikTok as an educational platform. The findings indicate that TikTok has become an effective medium for spreading religious messages, promoting Islamic values, and building religious communities among followers. TikTok allows for the dissemination of Islamic teachings, including the Quran and other educational content, through various formats such as images, videos, and stories. Moreover, the research shows that TikTok positively influences the understanding and practice of religion in this generation by providing easy access to religious information and support from religious communities. However, the study also highlights potential negative impacts, such as the spread of misinformation or radicalization, if not properly monitored.